18. EVALUATE THE LEVEL OF HEMOGLOBIN CONCENTRATION AND RELATED FACTORS IN WORKERS’S MEDICAL CHECKUP RESULT AT LE VAN THINH HOSPITAL, 2024 (Vietnam Journal of Community Medicine, 2024)
Objective: Research on 506 workers at a steel factory who came for a health check-up at Le Van Thinh Hospital to determine hemoglobin concentration and the influence of factors such as age, gender, and job position on this index.Research objects and methods: The study describes a series of cases, quantifying biology markers including red blood cell count, hemoglobin concentration and ferritin. The data was analyzed with STATA 14.0 software, using T test and ANOVA for statistical analysis.Results: The majority of workers were not anemic, accounting for 95.1%, the remaining 4.9% were mildly anemic. There is no difference in red blood cell count and hemoglobin concentration between genders and ages, but there is a statistically significant difference (p < 0.05) between job positions and hemoglobin concentration, in which people workers in manufacturing and stamping workshops have higher red blood cell counts, hemoglobin and ferritin concentrations than those working in offices.Conclusion: The difference is statistically significant between job functions, showing that the working environment and job tasks have an impact on hematological indicators, requiring more health protection measures for people, espicially workers in high-risk areas.
Keywords: Hemoglobin level; occupational diseases; periodic health examination